Intraosseous posterior superior alveolar artery distribution relative to maxillary teeth - Carsen R. McDaniel (Elsevier, 2024)
OBJECTIVES: Discuss which factors, if any, lead to increased identification of the intraosseous branch of the posterior superior alveolar artery within the lateral wall of the sinus. Assess the distance from the CEJ of posterior teeth to the intraosseous branch of the posterior super alveolar artery. METHODS: 254 cone-beam computed tomography (CBCT) scans of maxillary sinuses acquired using two scanners were analyzed for identification of the intraosseous branch (IoBr) of the posterior superior alveolar artery. The distance between the cementoenamel junction (CEJ) and IoBr was recorded at each maxillary posterior tooth position. Binomial logistic regression and multiple linear regression were used to evaluate the effects of scanner type, CBCT parameters, sex, and age on IoBr detection and CEJ-IoBr distance, respectively. P-values < 0.05 were used to determine significance. RESULTS: Mean CEJ-IoBr distances at second molar, first molar, second premolar, and first premolar positions were 17.0 ± 4.0 mm, 21.8 ± 4.1 mm, 19.5 ± 4.7 mm, and 19.9 ± 4.9 mm (scanner 1) and 17.3 ± 3.5, 16.9 ± 4.3, 18.5 ± 4.1, and 18.4 ± 4.3 (scanner 2). The independent variables had no statistically significant effect on IoBr detection. Tooth position (b = -0.67, P < .001) and scanner type (b = -1.3, P = 0.001) were statistically significant predictors of CEJ-IoBr distance. CONCLUSIONS: Estimations of CEJ-IoBr distance using CBCT appear comparable with previous cadaver, CT and CBCT based studies. CBCT scanner type may have a minor influence on this parameter. None of the independent variables had a significant effect on IoBr detection. IMPLICATIONS: Through this project, we determined that increasing resolution of CBCT imaging in order to increase identification of the intraosseous branch is not indicated. Furthermore, we determined that a given CBCT imaging system and tooth position may have a significant impact of the distance from the cementoenamel junction of posterior teeth to the inferior border of the intraosseous branch of the posterior superior alveolar artery.